Da terra ao céu: elementos de Moçambicanidade e do período pós- colonial presentes nos contos "o cachimbo de Felizbento" e "o homem cadente", de Mia Couto - Costa, Sayonara Souza da (2017)
Issues pertaining to the field of sociological studies, as well as questions concerning historicity, are important elements related to the national identity formation of a country. Literature may turn into a mechanism to promulgate such questionings, since it absorbs much of the socio-historical time through which a community passed and/or has been passing; therefore, it is an important source of investigation. For this reason, the present research aims at gathering remarks, reflections, and analyses of the African Literature, specially of the one of Mozambique, which is represented by Mia Couto’s work. The corpus of the present study is made up of the short stories “O cachimbo de Felizbento”, which is included in the Estórias abensonhadas collection (2012), and “O homem cadente”, which is contained in the book O fio das missangas (2009). Aiming at discussing the relationships among characters of the chosen works, as well as the depicted settings, the cultural elements and the way that the plot is related to the adopted research study, we will try to verify, in the stories to be analyzed, how the postcolonial period and the ideals of liberty, as well as the individual and his or her identity, are applied in the short stories. As theoretical approaches, we will use, among others, the postulates proposed by Rita Chaves (1998), Russeall Hamilton (1999), Stuart Hall (2003), Jane Tutikan (2006), Ana Mafalda Leite (2010).